(untitled) (Economics and region, 2023)
The topic of the article reveals the complex and controversial problem of forming new priorities, principles and mechanisms of global management. At the same time, it is recognized that the traditional management paradigm can no longer satisfy the realization of the strategic interests of either states, corporations, or organizations, which is why alternative centers of global power are gradually being singled out and formed, which try to be extraterritorial and absorb into their own structure, first of all, financial credit institutions, as well as industrial innovation and resource distribution centers. The purpose of the study is to determine the key elements of reinstitutionalization and its organizational design in the conditions of deepening conflict realities and the emergence of new alternative centers of global power. It is emphasized that the result of this is an alternative global government formed on the principle of a syndicate, which determines a favorable market situation and the main directions of monetary policy. It is emphasized that the new management paradigm, built on the network principle, will include several institutional levels under the control of which will be the sovereign economic prerogatives of a significant number of national states. In particular, we are talking about currency regulation, atomic energy, armed forces, raw resources, etc. By establishing new UN powers and launching new institutions of global governance, these traditional areas of national sovereignty are supposed to be delegated to global authorities. It is emphasized that the problem of preserving national economic sovereignty can be solved only by states with certain strategic development orientations that have the appropriate resource and demographic potential. As a conclusion, the idea is proposed that the destruction of the new management paradigm and the formation of a new one will occur as a result of the practical inability of most existing institutions to foresee and solve global problems, the key of which is the lack of effective control tools for the accumulation and redistribution of the resource base.